Analisis Kapasitas Tampung pada Lahan Basah Sei Kelik Ketapang - Hari Wibowo (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
Wetlands have a very important role for humans and the environment. The function of wetlands as a support for human life, among others, water sources, a variety of habitats for living things, controlling floods, and drought. One of the wetlands in the Kelik river, Ketapang Regency. This wetland has an area of 2600 ha. The land is now a conservation area, with cultivation rights. The existing problem, namely, the land is the residual combustion that occurred in 2015 and is always flooded with water and the need for an existing drainage system on the land. Land needs to be managed properly in water management. Efforts to manage conservation areas so as not to experience drought, which results in fires, which will threaten land conservations. Methods for dealing with drainage systems by utilizing existing ditches or drains. Drainage design using hydrological and hydraulic studies. The method used in determining the flood discharge plan is based on the need for drainage modulus and the area of the ArcGIS software aid sub-area. The results of the study indicate the need to improve the existing channel. Repair through efforts to deepen the trenches and hold widening or normalization. Also, the depth of the new channel is needed to make an automatic door so that the water can be grounded to maintain the availability of water in the ground.